Empowerment of Dermo Youth Organization with design training, welding techniques and OHS towards the development of economic independence of village communities - Iis Siti Aisyah; Ali Mokhtar; Dini Kurniawati; Nur Hasanah (Universitas Muhammadiyah Malang, 2024)
Unemployment may cause problems for those who experience it for example depression and cause other social problems including criminal acts such as thuggery. This problem can only be eliminated if the root cause of unemployment is eliminated. Eliminating unemployment must be done comprehensively although every region always has unemployment due to various factors, and it would be wiser if in overcoming the problem of unemployment and its side excesses such as thuggery, the local potential of the region and the communal approach are put forward. Handling of these social problems will be applied in Dermo Hamlet, Dau Subdistrict, where many welding workshops are located, yet there are still many people of productive age who do not have permanent jobs or are unemployed. So that the proposed Science and Technology-Based Community Service program in collaboration with Youth Organization partners in Dermo Hamlet aims to overcome these social problems through organizing design training, welding training and OHS / Occupational Health and Safety socialization. The initial capital constraints in making this business even though it is simple are related to the funding budget that is still not available to buy welding equipment and other supporting tools, besides that it is also constrained related to skills. So that in this PKM, 1 set of welding machines is provided. And the indicator of program achievement is marked by understanding of the material by giving 10 Basic Welding certificates and 10 OHS certificates from the Mechanical Engineering Study Program.